Offshoring call centers for emerging markets: findings from Brazil - Gião, Paulo Roberto; Oliveira Júnior, Moacir de Miranda (Internext, 2008)
Offshoring production and services is changing business models in many industries. Many manufacturing sectors and more recently service sectors are moving their plants or installations abroad, to affiliates or third-party companies in developing countries. This movement is also happening in the call center industry since India is the destination for many call centers, Brazil as well as presents good perspectives based on its multicultural society and the stage of the Brazilian call center industry. To understand and identify the potential capabilities and opportunities in this industry, a survey was carried out sampling 114 call centers located in Brazil. The main data shows the competitiveness of Brazil along with other emerging countries. Offshoring call centers are on the way up and Brazil has the capability to be a great player as the presented cases show. Results obtained from the survey demonstrate that Brazilian call centers are in the initial stage of internationalization, but that can change very quickly because the main infrastructure and human resources already exist and can be readied based on the technologies and competencies to serve international markets.